Plant Salinity Stress: Many Unanswered Questions Remain - Isayenkov, Stanislav V.; Maathuis, Frans J. M. (Frontiers in Plant Science, 2019)
Salinity is a major threat to modern agriculture causing inhibition and impairment of crop growth and development. Here, we review recent advances in salinity stress research in plants but also revisit some basic perennial questions that still remain unanswered. In this review we analyse the physiological, biochemical, and molecular aspects of Na+ and Cl+ uptake, sequestration and transport associated with salinity. We discuss the role and importance of symplastic versus apoplastic pathways for ion uptake and critically evaluate the role of different types of membrane transporters in Na+ and Cl- uptake and intercellular and intracellular ion distribution. Our incomplete knowledge regarding possible mechanisms of salinity sensing by plants are evaluated. Furthermore, a critical evaluation of the mechanisms of ion toxicity leads us to believe that, in contrast to currently held ideas, toxicity only plays a minor role in the cytosol and may be more prevalent in the vacuole. Lastly, the multiple roles of K+ in plant salinity stress are discussed.